SEARCH FOR RELIABLE PRECURSORS: A CASE STUDY OF THE SEISMIC QUIESCENCE OF THE 2000 WESTERN TOTTORI PREFECTURE EARTHQUAKE - Huang Q. (My University, 2006)
How to search for reliable precursors is one of the key problems of the study on earthquake forecast. In this paper a method is presented to judge whether or not a precursor is reliable. Before a potential anomaly can be nominated as a reliable precursor, it should pass or be proved by the following tests or analyses: whether or not it is an artificial anomaly, whether or not it correlates with an investigated event, whether or not it is a random anomaly. As a case study, I have investigated the reliability of seismic quiescence for an M = 7.3 earthquake, which occurred in the western region of Tottori prefecture, Japan, on 6 October 2000. The earthquake data (1975-2000) of the Japan Meteorological Agency (JMA) were used in this study. After analyzing the completeness of the catalog and removing aftershocks, a statistical method, which is called the RTL (region-time-length) algorithm and takes into account the information of magnitude, occurrence time and location of earthquakes, was applied to the above preprocessed earthquake data. A clear seismic quiescence anomaly was detected before the 2000 western Tottori prefecture earthquake. Close investigation indicated that the above anomaly is not due to artifacts of the selections of model parameters. After quantifying the anomaly and making statistical analysis over the whole investigated spatiotemporal domain, reasonable correlation between the above anomaly and the main shock in 2000 was recognized. The stochastic test using synthetic randomized catalogs showed the above anomaly is unlikely due to chance. Thus the above seismic quiescence anomaly before the 2000 main shock should be a significant and reliable precursor and the research method revealed in this study can enhance the reliability of precursors. Copyright 2006 by the American Geophysical Union.